(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Kalmishak has some ability of removal of inorganic matter. Objective: The purpose of the present study was to see the ability of Kalmishak for the removal of arsenic from isolated liver tissues of rat. Methodology: This animal study was carried out on isolated liver tissues of Long Evans Norwegian adult healthy male rats weighing 160 to 200 g. The rats were 3 to 6 months of age obtained from animal house of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from 2004 to 2005. Measurements and all tasks were performed in a very careful manner. Atomic Absorption Spectrophotometer with Hydride Generator was used to measure the arsenic level. No arsenic was added in test tube I. 2.5 g/ml arsenic trioxide was added rest of the test tubes. They all were incubated for 45 minutes at 370C. Then the tissues were washed properly. In second incubation, different extracts of kalmishak (C 1and C 2) were added at 20 l/ml dose. Second incubation was also for another 45 minutes at 370C. There were duplicates of all test tubes. Result: When the tissues were incubated with no arsenic in both 1st and 2nd incubation the amount of arsenic was found 6.62 ± 3.40 μg / g (mean ± s.e) of protein and it was considered as blank. The liver tissues of rat loaded with 2.5 μg / ml arsenic were incubated for 45 minutes at 37°C with no extract and the amount of arsenic was 98.32 ± 36.10 μg / g (mean ± s.e) of protein and the value was considered as standard. The blank value was then deducted from the standard and the derived value was considered as control. After exposure with Compound -1 (20 μl /ml) in second incubation for 45 minutes at 37°C, the amount of arsenic was 69.57 ± 7.60 μg / g (mean ± s.e) of protein. There was 13.00% removal of arsenic. Conclusion: In conclusion Kalmishak has the ability to remove of arsenic from isolated liver tissues of rat. Journal of Current and Advance Medical Research 2020;7(2): 55-59